RETRACTED: Advanced strategies for cognitive and emotional coping among high school students - Sitinjak, Charli; Rakhmawati, Ellya; Almasitoh, Ummu Hany; Setianingtyas, Anna Febrianty (INSPIRA: Indonesian Journal of Psychological Research, 2024)
This article has been retracted: please see INSPIRA: Indonesian Journal of Psychological Research Retraction, Withdrawal, & Correction (R-W-C) Policy (https://journal.iainlangsa.ac.id/index.php/inspira/rwc-policy). This article has been retracted at the request of the corresponding author. The corresponding author claimed the article had been submitted to another journal.